2008
DOI: 10.1051/0004-6361:20078888
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of collisional depolarization of the Ba II ${\lambda}$4554 line in the low chromosphere

Abstract: Context. Rigorous modeling of the Ba ii λ4554 formation is potentially interesting since this strongly polarized line forms in the solar chromosphere where the magnetic field is not very well known.Aims. We investigate the role of isotropic collisions with neutral hydrogen in the formation of the polarized Ba ii λ4554 line and, thus, in the determination of the magnetic field.Methods. Multipole relaxation and transfer rates of the d-and p-states of Ba ii by isotropic collisions with neutral hydrogen are calcul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 14 publications
1
23
0
Order By: Relevance
“…In modeling the Ba ii D 2 line we account for the depolarizing effects of elastic collisions with hydrogen atoms but neglect the alignment transfer between the 2 P 3/2 level and the metastable 2 D 5/2 level. It has been shown by Derouich (2008) that this alignment transfer affects the line center polarization and is needed for magnetic field diagnostics. The purpose of the present paper is however not to determine magnetic fields but to clarify the physics of line formation.…”
Section: Discussionmentioning
confidence: 99%
“…In modeling the Ba ii D 2 line we account for the depolarizing effects of elastic collisions with hydrogen atoms but neglect the alignment transfer between the 2 P 3/2 level and the metastable 2 D 5/2 level. It has been shown by Derouich (2008) that this alignment transfer affects the line center polarization and is needed for magnetic field diagnostics. The purpose of the present paper is however not to determine magnetic fields but to clarify the physics of line formation.…”
Section: Discussionmentioning
confidence: 99%
“…We notice that in the line wings, which are not sensitive to the Hanle effect, the polarization obtained with the BOM value for the elastic collision rate is in slightly better agreement with the observed profile. As far as depolarizing collisions are concerned, recently Derouich (2008) has shown that in the low chromosphere, where (2) depolarizing collision rate is much smaller than the line radiative transition rate, the depolarization of the 2 P 3/2 level is mainly due to alignment transfer with the D 3/2,5/2 metastable levels of Ba ii. The corresponding depolarization increases when the hydrogen density increases, because the alignments of the metastable 2 D 3/2,5/2 levels are vulnerable to collisions.…”
Section: Sensitivity To Elastic Collisionsmentioning
confidence: 99%
“…This might affect the line polarization at the wavelengths of the two secondary peaks due to the odd isotopes, but not in the central peak nor in the line wings. Furthermore, it is very likely that any ground level polarization would be destroyed by elastic collisions with hydrogen atoms, as is the case for the metastable 2 D 5/2 levels (see Derouich 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Our aim is to provide a correction factor on the theoretical value of the line linear polarization obtained by solving the non-LTE radiative transfer problem in the framework of two-level modeling. In this sense, we recall that Faurobert et al (2009) used a correction factor determined by Derouich (2008) for the Ba  λ4554 line; they found that, using a correction factor, the accuracy on the magnetic field has been improved by ∼50%.…”
Section: The Correction Factor F Cmentioning
confidence: 96%
“…(3) given in Derouich (2008). Physically, the collisional relaxation rates R k (J) correspond to the loss of atomic polarization and, in contrast, the transfer rates C k I (J l → J) and C k S (J u → J) correspond to the gain of atomic polarization coming from other levels.…”
Section: Summary Of the Theory Of Depolarizing Collisionsmentioning
confidence: 99%